2016
DOI: 10.1007/s00572-016-0691-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-specific symbiotic germination of Cynorkis purpurea (Thouars) Kraezl., a habitat-specific terrestrial orchid from the Central Highlands of Madagascar

Abstract: Orchids, particularly terrestrial taxa, rely mostly on basidiomycete fungi in the Cantharellales and Sebacinales that trigger the process of seed germination and/or initiate the full development of the seedling. During the course of development, orchids may associate with the same fungus, or they may enlist other types of fungi for their developmental needs leading to resilience in a natural setting. This study examined in vitro seed germination and seedling developmental behavior of Cynorkis purpurea, a terre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 58 publications
4
39
1
Order By: Relevance
“…However, our results suggest that either Phytamax TM is not well suited for P. coriacardia germination in vitro, or the germination of this species is particularly slow. We believe that the nutrient richness of this medium may be inhibitory to germination of P. coriacardia seeds, as previously demonstrated with other orchid species (Rafter et al 2016). We are cautious to suggest a highly specialized relationship with P. coriacardia, despite our results, because we only isolated fungi from adult plants, and as it has been reported, mature plants are not implicated in the symbiotic germination of orchids seeds (Ovando et al 2005).…”
Section: Orchid Species Description-pleurothallis Coriacardiasupporting
confidence: 50%
“…However, our results suggest that either Phytamax TM is not well suited for P. coriacardia germination in vitro, or the germination of this species is particularly slow. We believe that the nutrient richness of this medium may be inhibitory to germination of P. coriacardia seeds, as previously demonstrated with other orchid species (Rafter et al 2016). We are cautious to suggest a highly specialized relationship with P. coriacardia, despite our results, because we only isolated fungi from adult plants, and as it has been reported, mature plants are not implicated in the symbiotic germination of orchids seeds (Ovando et al 2005).…”
Section: Orchid Species Description-pleurothallis Coriacardiasupporting
confidence: 50%
“…4a, b). In orchids, mycorrhizal symbionts may switch in different developmental stages (McCormick et al 2004;Rafter et al 2016). Previous studies have demonstrated that compatible fungi for promoting seed germination may not be able to support subsequent seedling development (Bidartondo and Read 2008;Huynh et al 2009;Rasmussen et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Germination success was categorized into three stages and scored as described by (Arditti, 1967) with slight adjustments (Table 1). To avoid the possibility that embryo swelling (stage 1) was the result of water imbibition and not the result of a true association with the fungus (Rafter et al, 2016), only seeds that reached stage 2 or more advanced stages were considered to have truly germinated. Seed germination success was assessed by calculating the number of seeds reaching stages 2 and 3 divided by the number of viable seeds (i.e., protocorm formation) and the number of seeds developing into a seedling divided by the number of viable seeds (i.e., seedling development).…”
Section: In Vitro Seed Germinationmentioning
confidence: 99%